Origin Of Myopia in Children And Measures for Its Prevention (Eurasian Scientific Herald, 2024)
The work examines a disease such as myopia, which is a common disease. In childhood, especially during school years, myopia (myopia) is most common, which can be congenital or acquired. Features of the occurrence and progression of myopia in childhood and its prevention